Comparison of performances of industrial scale inclined bed paddy dryers - Sarker, Md. Sazzat Hossain; Ibrahim, Mohd Nordin; Ab. Aziz, Norashikin; Punan, Mohd Salleh (Faculty of Engineering, Universiti Putra Malaysia, 2012)
An investigation was done to evaluate the overall performance of industrial inclined bed dryers (IBDs) in the two paddy processing complexes of Padiberas Nasional Berhad (BERNAS). Attempts have been made in analyzing drying characteristics, energy consumption and final quality of dried product during drying of freshly harvested high moisture Malaysian paddy (MAR-219). The overall results from the present IBD drying practices exhibited the lack of consistency in operating parameters such as drying air temperature, drying time and air flow rate between the two complexes even among the IBDs in each complex. Consequently, variation in moisture reduction, drying capacity, energy consumption and rice quality happened. In reducing paddy moisture from 22.5- 23 % wet basis (wb) initial moisture content to around 12.5 % wb final moisture content, the drying capacity of the dryers were found to be varied between 0.656 and 1.03 ton dry paddy per hour, while the holding capacity of each dryer was 15 ton. The thermal energy consumption of the IBDs varied from 2.28 to 5.16 MJ/kg water evaporated while electrical energy consumption was found to be 0.55 to 0.75 MJ/kg water removed. Almost same initial moisture content paddy dried using lower drying temperature of 38-39 °C with IBD yielded 1 to 4 % higher head rice yield while milling recovery and whiteness were comparable at acceptable milling degree and transparency . Below 23 % wb moisture paddy, it is recommended that drying air temperature should not be higher than 39 °C in order to maintain rice quality and minimize energy consumption.